2009
DOI: 10.3310/hta13550
|View full text |Cite
|
Sign up to set email alerts
|

VenUS II: a randomised controlled trial of larval therapy in the management of leg ulcers

Abstract: EA Nelson and DJ Torgerson on behalf of the VenUS II teamHow to obtain copies of this and other HTA programme reports An electronic version of this publication, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable CD-ROM is also available (see below).Printed copies of HTA monographs cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our Despatch Agents.Non-UK purchasers will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 266 publications
0
73
0
1
Order By: Relevance
“…Dumville et al in the UK in 2009 conducted the largest RCT. 25 They included 267 venous or mixed venous arterial ulcers that were treated either with MDT (free living or loose larvae) or hydrogel, and followed up for 12 months in a three-armed trial. They concluded that "Larval therapy did not improve the rate of healing of sloughy or necrotic leg ulcers or reduce bacterial load compared with hydrogel but did significantly reduce the time to debridement and increased ulcer pain."…”
mentioning
confidence: 99%
“…Dumville et al in the UK in 2009 conducted the largest RCT. 25 They included 267 venous or mixed venous arterial ulcers that were treated either with MDT (free living or loose larvae) or hydrogel, and followed up for 12 months in a three-armed trial. They concluded that "Larval therapy did not improve the rate of healing of sloughy or necrotic leg ulcers or reduce bacterial load compared with hydrogel but did significantly reduce the time to debridement and increased ulcer pain."…”
mentioning
confidence: 99%
“…No significant differences were seen in the bacterial burden and in the rate of MRSA colonization in the different study groups [34]. …”
Section: Epithelialization Possiblementioning
confidence: 95%
“…Medical maggots of the common green bottle fly (Lucilia sericata) are used as free-range or contained in biobags of polyvinyl material. With respect to efficacy of free-range versus biobags the data are controversial at present [32][33][34]. The maggot secretions (leucine aminopeptidases, collagenases, among others) lyse necrotic tissue while sparing vital tissue.…”
Section: Biological Debridementmentioning
confidence: 99%
“…7,61 There was no evidence of a difference in recurrence of healed ulcers and few people had a recurrence within trial follow-up.…”
Section: Key Findingsmentioning
confidence: 99%
“…61 Taking the time to healing as an example, in this IPW approach only participants with observed time to healing data contribute with non-zero terms, but their contributions are inversely weighted by the probability of being observed. 61 Consequently, individuals who are less likely to be observed are weighted most heavily. The censoring distribution was estimated through the Kaplan-Meier estimator.…”
Section: Datamentioning
confidence: 99%